Enhanced Hand Function Assessment Using Pressure: Mapping and Low Cost Motion Capture. (September 2014) - Figueroa, Rosemarie; Das, Shwetarupalika; Armstrong, Thomas; Woolley, Charles; Chung, Kevin
Hand injuries affect our ability to manipulate objects, and existing tools are useful in determining if patients have difficulty performing tasks. The Jebsen–Taylor Hand Function Test (JTT), is a widely used test for functional motor assessment that reflects activities of daily living. But current tools, including the JTT, do not measure compensatory behavior. This study aimed to investigate the use of a low cost motion capture system to evaluate compensatory behavior of Rheumatoid Arthritis (RA) patents during a JTT assessment. Youth and Older control groups were used as a basis for comparison of RA patient performance. Results of the JTT itself illustrated how RA patient can perform some tasks more quickly than control groups. However, the JTT only evaluates completion times of each task, not how the participant performed the activity. Including Range of Motion measurements during this JTT assessment indicated that there are significant differences in the Range of Motion of RA patients in comparison to both young and older control groups. For example, hand displacement results for the RA participants were significantly greater than those of the older control. This demonstrates that the integration of motion capture analysis with the JTT gives a more comprehensive assessment of hand function.